"I Like it!" Preference Actions Separated from Hedonic Reactions. Issue 3 (7th March 2016) - Booth, David A.
Abstract: In 1952–1957, Peryam and colleagues developed nine ordinal phrases of liking and dislike to assess consumers' dispositions to accept or reject a food or drink. They named their questionnaire a Food Preference Scale. Others called it the Hedonic Scale, which means assessment of pleasure, not choice. It is still widely assumed that the word "like" distinguishes felt pleasure from observed wanting to consume the sample. The quantitative results presented here complement an earlier qualitative finding that preference scores do not provide evidence of the experiencing of pleasure. Rather, "I like it!" simply indicates high acceptance of the sampled variant of a product. Nevertheless, in this experiment, some assessors did also get a convulsive thrill from oral stimulation, as distinct from just enjoying the mouthful, or being pleased by it. However, this sensual pleasure came only from strongly disliked levels of stimulation and is probably unique to samples sensed as intensely sweet. Practical Applications: This experiment's separation of preference from pleasure depended on overcoming practitioners' division between sensory vocabulary and preference scores. Instead of seeking statistical patterns that bridge the supposed gap between sensory concepts and acts of acceptance, sensory studies should design test samples capable of measuring the impact of specified variations in the product range, first on a fully integrative judgment such as match to the personal ideal, or to the most familiar or usual brand. Second, if analytical characterization might help to test the specification, samples can be rated on vocabulary learned in life or in the laboratory, with one anchor on the standard to be matched, such "exactly as I like it" or "just right" (not "like extremely" or "just about right"), and only one other anchor, such as "neither like nor dislike" or "just too wrong to be tolerable." Existing data collection and analysis software are easily adapted this way.